Solve for t (2(t-4))/3=8

Math
2(t-4)3=8
Multiply both sides of the equation by 32.
32⋅2(t-4)3=32⋅8
Simplify both sides of the equation.
Tap for more steps…
Simplify 32⋅2(t-4)3.
Tap for more steps…
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
32⋅2(t-4)3=32⋅8
Rewrite the expression.
12⋅(2(t-4))=32⋅8
12⋅(2(t-4))=32⋅8
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
12⋅(2(t-4))=32⋅8
Rewrite the expression.
t-4=32⋅8
t-4=32⋅8
t-4=32⋅8
Simplify 32⋅8.
Tap for more steps…
Cancel the common factor of 2.
Tap for more steps…
Factor 2 out of 8.
t-4=32⋅(2(4))
Cancel the common factor.
t-4=32⋅(2⋅4)
Rewrite the expression.
t-4=3⋅4
t-4=3⋅4
Multiply 3 by 4.
t-4=12
t-4=12
t-4=12
Move all terms not containing t to the right side of the equation.
Tap for more steps…
Add 4 to both sides of the equation.
t=12+4
Add 12 and 4.
t=16
t=16
Solve for t (2(t-4))/3=8

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top